Hidrodinamsko-mehanski vplivi v napravi za posnemanje gibanja želodca in črevesja na trdne dostavne sisteme za peroralno aplikacijo - Vrbanac, Helena (visokošolska dela, 2021)
Due to many advantages - such as e.g. large area of the gastrointestinal tract (GIT) available for the drug absorption, the presence of different pH compartments that facilitate dissolution of the poorly soluble drugs, patient comfort and thus greater compliance, and also favourable economic aspects - the oral route of administration remains the most commonly used way of drug application. Understanding the physiological factors of the digestive tract and their influences on the ingested medicine effectiveness is therefore crucial for the rational design of a new formulation. For this purpose, in vitro dissolution tests are performed, which are important element in the early and late stages of a new formulation development. Good in vitro-in vivo correlation (IVIVC) is an important tool for the in vivo results prediction, based on available in vitro data, as it enables the optimisation of the new formulation development and reduces the number of the required clinical studies. For the evaluation of the solid dosage forms, standardized dissolution devices are mainly in use. However, growing complexity of the new drug delivery systems and the increase of the poorly soluble drugs require individual and multidisciplinary evaluation and prediction of the drug release. Therefore, there is a need of biorelevant dissolution methods able to capture physiological conditions of the GIT. Examples of such biorelevant methods are also artificial gastric and intestinal simulator - the main topic of our research. The aim of the doctoral dissertation was measurement-supported simulation of the physiological processes on the both devices, as they can be found described from the in vivo studies and which can significantly affect in vivo drug release. New methodologies have been developed and evaluated to monitor and characterize these influences. In this manner, a program sequence on an artificial gastric simulator that mimics fasting gastric movement was developed. Additionally, the importance of gastric emptying for immediate release dosage forms was evaluated. Moreover, the effect of organ passage for the dosage forms with poorly soluble active ingredients and the effect of the simultaneous presence of food in the GIT on the drug release from mechanically sensitive hypromellose (HPMC) tablets was evaluated. After ingestion, the dosage forms are exposed to strong mechanical stress, mainly due to the movement of the gastric wall and the passage through the sphincters. An example of such movement is also the migrating motor complex (MMC). The main characteristics of this pattern of movement and pressure load were captured with the developed program sequence on an artificial gastric simulator. The mechanical biorelevance of the prepared sequence was verified with SmartPill capsule measurements. The in vitro obtained motility parameters of the developed movement regime were correlated with the obtained set of comparable in vivo data from the published literature. To illustrate the mechanical effect of the prepared sequence on the ingested dosage form, mechanically sensitive HPMC tablets, previously included in in vivo experiments, were used. The prepared program sequence had a significant effect on the drug release from the tested HPMC tablets. Compared to the experiments, conducted in a standardized dissolution apparatus - paddle device, the artificial gastric simulator showed greater discriminatory power in recognizing the differences between the tested HPMC tablets, in accordance to in vivo data. We believe that described optimization of the device is a step closer in enabling physiologically relevant conditions of the dissolution testing. Further, the effect of the GIT transit on the micro-environmental pH (pHM) in the gel layer of the HPMC matrix tablets containing drugs with pH-dependent solubility was studied. In addition to dissolution testing with the change of the acidic stomach environment into the basic intestinal environment, methods for determination of the pHM in the gel layer of the HPMC tablets were developed and evaluated. One such method was determination of the pHM with freezing the hydrated tablets and the use of the surface pH electrode, and the other with incorporation of the pH indicator dye into the tablet matrix. Due to the changed solubility, the influence of the simulated organ passage was shown to change the release kinetics of the model drug in all performed experiments, however, in the case of the mechanically biorelevant models statistically faster drug release compared to the conventional dissolution apparatus (paddle device) was observed. The method of incorporating a pH indicator into an HPMC tablet proved to be more appropriate, while the method of freezing tablets proved to be suitable only for a rough assessment of pH gradient establishment in the gel layer at organ transition. In the second part of the dissertation, the combination of food effect and mechanical stress on the model drug release (paracetamol) from the HPMC matrix tablets was examined. Such dosage forms stay in the digestive tract for a longer period and are thus subjected to a number of variable conditions, including e.g. food and sweet/alcoholic beverages intake, causing accelerated gastric movement and prolonged stress on the gastric content. In addition to the artificial gastric simulator, the mechanical effect was also studied using pharmacopoeial methods - paddle apparatus and reciprocating cylinder apparatus. Besides dissolution testing, the properties of the hydrated matrix tablets were evaluated with morphological observations and texture analyser. Our results suggest that the static dissolution methods exhibit poor ability to detect robustness of such formulations in the presence of osmotically active ingredients of dissolution medium. Moreover, the absence of the mechanical component has resulted in a seemingly higher influence of the high in fat and high in protein dissolution media, presumably due to the deposition of insoluble media components on the tablet surface - a process not expected to happen in vivo. We demonstrated that the use of mechanically biorelevant dissolution methods, such as e.g. advanced gastric simulator, could provide an additional insight into the HPMC matrix tablet behaviour under the simulated fed gastric conditions. In addition to the above-mentioned mechanical influences, changes in the environmental pH values and presence of the food in the digestive tract, one of the very important physiological process, dictating the amount of the drug available for absorption into the systemic blood circulation, is also gastric emptying. To this end, we prepared a gastric emptying regime in accordance with the main findings of the in vivo studies, performed under fasting conditions in accordance with EMA and FDA guidelines for conducting bioequivalence and bioavailability studies. The effect of the gastric emptying on the model drug release kinetics was studied with 4 immediate release dosage forms, previously included in in vivo testing. We have shown that, in comparison with conventional dissolution methods, prescribed by regulatory authorities, advanced gastric simulator is better at prediction of the in vivo release (absorption) profiles in the case of the tested formulations. Presented findings of the doctoral dissertation significantly contribute to the further development and optimisation of both innovative, biorelevant dissolution models, especially in terms of achieving greater similarity to in vivo conditions and a better explanation of the mechanisms behind the drug release kinetics. Set research problems, hypothesis and the selected methodology represent qualitative and substantive upgrade and continuation of the previously performed pioneering research.
Keywords: absorpcija zdravilnih učinkovin; disertacije; Farmacevtske oblike; kinetika sproščanja učinkovin; sproščanje zdravilnih učinkovin; tablete; Zdravilne učinkovine